2019
DOI: 10.15305/ijrci/v7i1/286
|View full text |Cite
|
Sign up to set email alerts
|

A rare co-occurrence of anti CCP-positive rheumatoid arthritis with sacroiliitis

Abstract: Sacroiliitis is considered as the most important sign of spondyloarthropathy. Rheumatoid arthritis mainly affects peripheral joints and the involvement of sacroiliac joint is very rare. The present case study discusses the rare existence of RA and concurrent chronic bilateral sacroiliitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…81 patients were included in the study here presented. Of these, 74 were those detected in the literature review [ 6 40 ] and 7 from our center. Of the total number of cases, 58 were men (71%), with a mean age of 53 years (±14.83), and a mean age of the onset of the disease was 34 years (±14.87).…”
Section: Resultsmentioning
confidence: 99%
“…81 patients were included in the study here presented. Of these, 74 were those detected in the literature review [ 6 40 ] and 7 from our center. Of the total number of cases, 58 were men (71%), with a mean age of 53 years (±14.83), and a mean age of the onset of the disease was 34 years (±14.87).…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Finally, the authors mentioned about HLA-B7 positive sacroiliitis with concurrent early anti-CCP positive RA and concluded that since the possibility for SpA had been excluded in current patient, the presence of sacroiliitis can be considered as an atypical joint involvement of RA. 1 However; in my opinion, the history of IBP, raised inflammatory markers, bilateral active sacroiliitis on MRI, and back pain not responding to RA treatment, but to NSAIDs, all these were actually fulfilling ASAS axial SpA criteria along with ACR/EULAR 2010 RA criteria. 5,6 The ASAS criteria for axial SpA are a step forward in the SpA arena and help diagnosing early non-radiographic axial SpA as well as established SpA.…”
Section: Ijrci 2020;8(1):c1mentioning
confidence: 88%
“…As per the authors, the magnetic resonance imaging (MRI) of SIJs had confirmed chronic bilateral sacroiliitis. 1 In my opinion, especially in rheumatology field, chronicity is to be documented as per time period, since symptoms/ signs present (inflammatory back pain (IBP) in this case) and not from the radiological techniques. In case of SIJs, plain radiograph actually gives information on grading of sacroiliitis (damage due to inflammation), while MRI gives information on active inflammation/ damage due to inflammation of SIJs .2, 3 In this particular case presented, it seems to be acute LBP (6 weeks duration) rather than chronic!…”
Section: Ijrci 2020;8(1):c1mentioning
confidence: 95%
See 2 more Smart Citations